Crypto "money": Perspective of a couple of Canadian central bankers - James Chapman; Carolyn A. Wilkins (Bank of Canada, 2018)
The market for cryptoassets has exploded in size in the 10 years since bitcoin was launched. The technology underlying cryptoassets, blockchain, has also been held up as a technology that promises to transform entire industries. In this paper we examine what is new about cryptoassets and their technology and how they may affect core central bank functions. We do this by outlining what we think are the three most important research and policy questions for central bankers around cryptoassets and cryptocurrencies specifically. First, what is fundamentally new about the technology that underpins cryptocurrencies and other cryptoassets? Second, how do cryptocurrencies affect a central bank's role in the economy? Third, given the two challenges of a rise of cryptoassets and a decline in the use of cash, should digital payments be left entirely to the private sector or should central banks issue their own digital currencies? We discuss these three policy questions and highlight what aspects of them are most important to central bankers. Finally, we raise several new questions to help guide researchers in studying cryptoassets and their underlying technology.
Keywords: E4; E41; E42; E51; E58; H4; P43; 330; Digital currencies; Payment clearing and settlement systems; Bank notes; Financial services